INTRACELLULAR GROWTH OF BACTERIOPHAGE STUDIED BY ROENTGEN IRRADIATION - Latarjet, Raymond (The Rockefeller University Press, 1948)
Growing Escherichia coli infected with bacteriophage T2 was x-rayed during the 21 minute latent period which elapses between infection and lysis of the cells. Survival curves of the infected bacteria were determined almost from minute to minute; they disclosed the following facts which are related to the process of phage growth: During the first 7 minutes, the infective virus particle remains in the cell unique and genetically intact. The host cell synthesizes some ultraviolet-absorbing material probably devoted to building future particles. From the 7th to 9th minute the x-ray resistance of the virus particle increases, probably because of some internal change. Then, multiplication starts and is completed at about the 13th minute, when an average of 130 virulent units is present per cell, displaying an x-ray resistance twice as high as that of the extracellular virus particle. From 13 minutes to the end, the new units progressively recover the x-ray sensitivity of the extracellular virus. Nothing can be said about either the rate of multiplication between 9 and 13 minutes, or the nature of the multiplying units, except that they are more radiation-resistant (probably smaller) than the extracellular virus. The first steps of the growth process are favored by an unknown component of the lysate, different from the active particles. Several particles can grow in the same host cell.